Socio-economic Factors Affecting the Choice of Transportation Mode in Jakarta Metropolitan Area - Maulana, Rizky; Yudhistira, Muhammad Halley (Universitas Diponegoro, Indonesia, 2020)
This study aims to analyze the effect of socio-economic factors on the choice of transportation mode. The socio-economic variables used in this study are income, education, sex, employment sector, motorcycle ownership, car ownership, city of origin, commuting distance, and a number of commuters in a household. The object of this study is a commuter worker in Jakarta Metropolitan Area. One of the main problems in JMA is traffic congestion. Recent studies stated that public transportation able to decrease the problem of congestion. However, for some reason, the commuters of JMA are reluctant to use it. With the 2014 Jabodetabek commuter survey, we obtain a result that eight of nine socio-economic variables used in this study are statistically significant. We use a multinomial logit method to estimate the model.